Oxygen-deficient perovskites for oxygen evolution reaction in alkaline media: a review - Ahmed Badreldin (9574341) (2022)
Oxygen vacancies in complex metal oxides and specifically in perovskites are demonstrated to significantly enhance their electrocatalytic activities due to facilitating a degree of control in the material’s intrinsic properties. The reported enhancement in intrinsic OER activity of oxygen-deficient perovskites surfaces has inspired their fabrication via a myriad of schemes. Oxygen vacancies in perovskites are amongst the most favorable anionic or Schottky defects to be induced due to their low formation energies. This review discusses recent efforts for inducing oxygen vacancies in a multitude of perovskites, including facile and environmentally benign synthesis strategies, characterization techniques, and detailed insight into the intrinsic mechanistic modulation of perovskite electrocatalysts. Experimental, analytical, and computational techniques dedicated to the understanding of the improvement of OER activities upon oxygen vacancy induction are summarized in this work. The identification and utilization of intrinsic activity descriptors for the modulation of configurational structure, improvement in bulk charge transport, and favorable inflection of the electronic structure are also discussed. It is our foresight that the approaches, challenges, and prospects discussed herein will aid researchers in rationally designing highly active and stable perovskites that can outperform noble metal-based OER electrocatalysts. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-020-00123-z